KARAKTERISASI CHAR PRODUK PYROLYSIS LIMBAH PLASTIK DAN UNJUK KERJANYA SEBAGAI BAHAN BAKAR BRIKET - , SUTOYO ([Yogyakarta] : Universitas Gadjah Mada, 2014)
Plasticâwaste recycling technology through pyrolysis process has proved able to produce useful products, and also able to reduce amount of redundant plastic waste with limitation landfill. Nowadays, there is still a kind of plastic-waste pyrolysis product which is not optimized in application that is char which is by product. Char materials in this research consists of 13 samples earned from pyrolysis of polyethylene plastic material (PE) with various operation temperature between 450-500ÂºC, and also various mass and Zeolite Y catalytic type and Natural Zeolite. Variations also conducted by mixing PE material with Polystyrene (PS) type, Polypropylene (PP), Polyethylene Terephthalate (PET), and Other. Char characteristic is acknowledged through proximate test covers moisture content, ash, volatile matter, and fixed carbon, calorie value is measured by bomb calorimeter. Further, materials is made into briquette for testing sample with composition 4 grams of char mixed 0,5-1 gram binder (1% tapioca starch and 90% water). Briquette is made cylindrically in 1,75 cm diameter with compression strength 10 kg/cm2 From overall tested briquette samples, 5 samples are mild and melted down when burned, thus only 8 samples which are deserved as briquette-fuel. Through emission testing covers content of CO, NO,NOx, and SO . Testing for briquette performance covers impact resistance index (IRI), combustion characteristic is tested in the furnace with wall temperature 230Â°C and constant air flow rate 0,7 m/s. Besides that, briquette emission content is also measured by making 3 grams-sample, then burned with constant hot air rate 350Â°C. 2 is obtained a result that emission content from the whole briquette samples are still within tolerance of safe limit.